Judet type-IV radial neck fractures in children: Comparison of the outcome of fractures with and without bony contact. (2nd September 2016) - Kaiser, Margarita; Eberl, Robert; Castellani, Christoph; Kraus, Tanja; Till, Holger; Singer, Georg
Abstract : Background and purpose — Heavily displaced radial neck fractures in children are sometimes associated with poor outcome. A substantial number of these fractures require open reduction. We hypothesized that Judet type-IV fractures with a completely displaced radial head would result in a worse outcome than radial neck fractures with remaining bony contact. Patients and methods — We analyzed 19 children (median age 9.7 (4–13) years) who were treated for Judet type-IV radial neck fractures between 2001 and 2014. The outcome was assessed at the latest outpatient visit using the Linscheid-Wheeler score at a median time of 3.5 (1–8) years after injury. The patients were assigned either to group A (9 fractures with remaining bony contact between the radial head and the radial neck) or to group B (10 fractures without any bony contact). Results — The 2 groups were similar concerning age and sex. The rate of additional injuries was higher in group B (7/10 vs. 1/9 in group A; p = 0.009). The rate of open reduction was higher in group B (5/10 vs. 0/9 in group A; p = 0.01). Poor outcome was more common in group B (4/10 vs. 0/9 in group A; p = 0.03). In group B, the proportion of children with poor outcome (almost half) was the same irrespective of whether open or closed reduction had been done. Interpretation — The main causes of unfavorable results of radial neck fracture in children appear to be related to the energy of the injury and the amount of displacement—and not to whether open reduction was used.